Association of tumor size in pathological T4 colorectal cancer with desmoplastic reaction and prognosis. Issue 5 (21st March 2022) - Shiraishi, Takuya; Ogawa, Hiroomi; Katayama, Ayaka; Osone, Katsuya; Okada, Takuhisa; Enokida, Yasuaki; Oyama, Tetsunari; Sohda, Makoto; Shirabe, Ken; Saeki, Hiroshi
Abstract: Background: Tumor size in pathological T4 (pT4) colorectal cancer (CRC) is associated with oncological prognosis; however, its relation to epithelial‐mesenchymal transition (EMT)‐associated histology is unclear. We aimed to investigate the association of tumor size with oncological prognosis and EMT. Methods: We performed a retrospective analysis of 95 patients with primary CRC who underwent radical surgery and were consecutively diagnosed with pT4. Results: Both 3‐y disease‐free survival (DFS) and cancer‐specific survival (CSS) were significantly higher in patients with tumor size ≥50 mm than in those with tumor size <50 mm ( P  = .009 and P  = .011, respectively). The independent factors identified in the multivariate analysis for DFS were pathological lymph node metastasis (hazard ratio [HR], 2.551; 95% confidence interval [CI], 1.031–6.315; P  = .043), distant metastasis (HR, 2.511; 95% CI, 1.140–5.532; P  = .022), tumor size (HR, 0.462; 95% CI, 0.234–0.913; P  = .026), and adjuvant chemotherapy (HR, 0.357; 95% CI, 0.166–0.766; P  = .008). The independent factors identified in multivariate analysis for CSS were tumor location (HR, 10.867; 95% CI, 2.539–45.518; P  = .001) and tumor size (HR, 0.067; 95% CI, 0.014–0.321; P  < .001). In pT4 CRC, smaller tumor size was associated with nonmature desmoplastic reaction and EMT‐related histology. Conclusions: Tumor size ≥50 mm was associated with a better DFS and CSS than that of <50 mm, in patients with pT4 CRC. Smaller tumor size with advanced invasion likely reflects a more biologically aggressive phenotype in pT4 CRC. Abstract : This retrospective study found a relationship between tumor size in colorectal cancer and epithelial‐mesenchymal transition‐related histology. In addition, this study found associations of tumor size with disease‐free survival and cancer‐specific survival.